2007
DOI: 10.1111/j.1745-7270.2007.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Potent α3/5 Conotoxins from Piscivorous <italic>Conus achatinus</italic>

Abstract: Every cone snail produces a mixture of different conotoxins and secretes them to immobilize their prey and predators. alpha3/5 Conotoxins, isolated from fish-hunting cone snails, target muscle nicotinic acetylcholine receptors. The structure and function of alpha3/5 conotoxin from the piscivorous Conus achatinus have not been studied. We synthesized two pentadecamer peptides, Ac1.1a and Ac1.1b, with appropriate disulfide bonding, based on cDNA sequences of alpha3/5 conotoxins from C. achatinus. Ac1.1a and Ac1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…Previous results suggested that some a3/5-conotoxins also exhibit asymmetric elution peaks on HPLC following oxidation, and have two conformations in aqueous condition [13,[21][22][23], which differ in the second Cys loop and peptide termini region [23]. It would be difficult to determine which conformer is more favorable for peptide activity on nAChRs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous results suggested that some a3/5-conotoxins also exhibit asymmetric elution peaks on HPLC following oxidation, and have two conformations in aqueous condition [13,[21][22][23], which differ in the second Cys loop and peptide termini region [23]. It would be difficult to determine which conformer is more favorable for peptide activity on nAChRs.…”
Section: Discussionmentioning
confidence: 96%
“…Oocytes of Xenopus laevis frogs were prepared and injected with capped RNA to elicit expression of mouse fetal skeletal-muscle and various rat neuronal nAChR subtypes as described previously in detail [12][13][14][15][16].…”
Section: Voltage Clamp Recordingmentioning
confidence: 99%
“…Because these alternatively cleaved forms are always less abundant than the full length mature peptide, their biological relevance is unclear. However, because conopeptides differing by only a few residues at their N-or C termini can have altered biological activity (61)(62)(63), this VPP is expected to have evolutionary significance. Together with the hypermutations seen at the mRNA level, VPP is a new mechanism that contributes to "biological messiness" in venoms, a concept recently developed in the field of enzymology to explain the origins of evolutionary innovation (64).…”
Section: Venomics Of Conus Marmoreusmentioning
confidence: 99%
“…With an estimated 50 to 200 peptide toxins produced by each Conus species (260), many useful toxins for nAChR research have yet to be characterized. Recently identified conotoxins are specific for different types of nAChRs: muscle-type nAChRs (261)(262)(263), α3β4 nAChRs (264), α3β2 and α7 nAChRs (265), α7-containing nAChRs (266), and α9α10 nAChRs (267). Conotoxin antagonism against α9α10 nAChRs showed both a role of α9α10 nAChRs in neuropathic pain and the potential therapeutic role of conotoxins (268).…”
Section: Neuronal Nachrsmentioning
confidence: 99%